Neighboring Extremal Solution for Nonlinear Discrete-Time Optimal Control Problems With State Inequality Constraints - Ghaemi, R.; Jing Sun; Kolmanovsky, I.V. (IEEE transactions on automatic control, 2009)
A neighboring extremal control method is proposed for discrete-time optimal control problems subject to a general class of inequality constraints. The approach is applicable to a broad class of systems with input and state constraints, including two special cases where the constraints depend only on states but not inputs and the constraints are over determined. A closed form solution for the neighboring extremal control is provided and a sufficient condition for existence of the neighboring extremal solution is specified.